Analisis Pengelolaan Dana Tabarru (Asuransi Jiwa Syariah) dalam Produk Pembiyaaan di BMT Mardhatillah Berkah Karawang - Dodi Hermawan; Asep Dede Kurnia; Moch. Cahyo Sucipto (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
Non-bank Islamic financial institutions such as BMT must be able to conduct a good financing risk management system so that the risks that occur can be minimized, while the efforts made by BMT Mardhatillah Berkah Karawang in minimizing it by charging each member who is doing Financing by paying Tabarru funds and that paid only once when members make funding disbursements. The purpose of this study is to determine the management of Tabarru funds in Financing Products at BMT Mardhatillah Berkah and to determine the implementation of the Tabarru contract which was carried out at the time of financing. Tabarru ’can be interpreted as donations, grants, benevolent funds, or alms. Whereas those who make donations are called mutabarri or generous. Based on the research results of each member who conducts Financing at BMT, Be it Murabahah, Mudharabah, and Rahn Financing, there will be Tabarru Funds that must be paid at the time of Funding Disbursement where Tabarru funds will be used to help each other or bear one another if there is a risk of death among BMT members. In the Tabarru contract, the Member gives a grant which will be used to help other BMT Members who experience an accident or an event that is outside of human will, so that the funds are separated from other funds.